UJI EFEKTIVITAS EKSTRAK ETANOL DAUN RAMANIA (Bouea macrophylla Griffith) TERHADAP MORTALITAS LARVA Artemia salina Leach - Gusti Rifda Aqiila; Irham Taufiqurrahman; Erida Wydiamala (FKG Unlam, 2017)
Background: Ramania is a typical local plant of Borneo. Ramania leaves contain secondary metabolic compounds i.e. flavonoid, saponin and triterpenoidwhich expected to be one of the alternatives for cancer treatment. Purpose: To analyzing the effectiveness of ethanol extract of ramania leaves against Artemia salina Leach larvae’s mortality using Brine Shrimp Lethality Test (BSLT). Methods: A true experimental research with post test only with control group design, using 8 treatment groups obtained by a preliminary test. Eight groups consisting of 7 extract concentrations i.e 156,25; 312,5; 625; 1250; 2500; 5000 dan 10000 mg/L and 1 control negative. Results: LC50 value by probit analysis test is 408,950 mg/L. The p-value of Kruskall-Wallis test is 0,000, there is a significant effect of ethanol extract of ramania leaves against Artemia salina Leach larvae’s mortality. The p-value of Mann-Whitney test is 0,021, there is a significant difference between negative control with all treatment groups. Conclusion: Ethanol extract of ramania leaves has effectiveness against Artemia salina Leach larvae’s mortality using Brine Shrimp Lethality Test (BSLT) with LC50 values of 408.950 mg/L.